MANAJEMEN PESERTA DIDIK BERBASIS PAMAHAMAN NILAI KARAKTER ISLAM DAN IMPLIKASINYA TERHADAP PERILAKU BERAGAMA - Abdul Mun'im Amaly; Toto Koswara; Giantomi Muhammad; Mohamad Erihadiana (Jurnal Al Burhan, 2021)
Today Islamic character education is much loved both in the world of education and in the community, to be able to implement this it needs to be managed in such a way, especially in the education management of students, the results of which will have implications for the religious behavior of the students themselves. This article aims to reveal student management based on the understanding of Islamic character values ??and their implications for religious behavior. This study uses a qualitative approach along with data collection techniques through observation, interviews, and documentation. The results showed that the management of students based on understanding the values ??of Islamic character at SMK Assyafiiyah was carried out by collaborating with various elements of education, both users, stakeholders, educators, education staff, and the entire school academic community. Optimizing the understanding of Islamic character values ??in learning assisted and guided by the teacher, and using five approaches, namely the cultivation of social values, cognitive development, value analysis, value clarification, and learning to do. This study concludes that by using student management steps and these approaches, student management based on the understanding of Islamic character values ??can have implications for students' religious behavior in their daily lives.